Quantifying the radiant exposure and effective dose in patients treated for actinic keratoses with topical photodynamic therapy using daylight and LED white light. (25th January 2018) - Manley, M; Collins, P; Gray, L; O'Gorman, S; McCavana, J
Abstract: Daylight photodynamic therapy (dl-PDT) is as effective as conventional PDT (c-PDT) for treating actinic keratoses but has the advantage of reducing patient discomfort significantly. Topical dl-PDT and white light-PDT (wl-PDT) differ from c-PDT by way of light sources and methodology. We measured the variables associated with light dose delivery to skin surface and influence of geometry using a radiometer, a spectral radiometer and an illuminance meter. The associated errors of the measurement methods were assessed. The spectral and spatial distribution of the radiant energy from the LED white light source was evaluated in order to define the maximum treatment area, setup and treatment protocol for wl-PDT. We compared the data with two red LED light sources we use for c-PDT. The calculated effective light dose is the product of the normalised absorption spectrum of the photosensitizer, protoporphyrin IX (PpIX), the irradiance spectrum and the treatment time. The effective light dose from daylight ranged from 3 ± 0.4 to 44 ± 6 J cm −2 due to varying weather conditions. The effective light dose for wl-PDT was reproducible for treatments but it varied across the treatment area between 4 ± 0.1 J cm −2 at the edge and 9 ± 0.1 J cm −2 centrally. The effective light dose for the red waveband (615–645 nm) was 0.42 ± 0.05 J cm −2 on a clear day, 0.05 ± 0.01 J cm −2 on an overcast day and 0.9 ± 0.01 J cm −2 using the white light. This compares with 0.95 ± 0.01 and 0.84 ± 0.01 J cm −2 for c-PDT devices. Estimated errors associated with indirect determination of daylight effective light dose were very significant, particularly for effective light doses less than 5 J cm −2 (up to 83% for irradiance calculations). The primary source of error is in establishment of the relationship between irradiance or illuminance and effective dose. Use of the O'Mahoney model is recommended using a calibrated logging illuminance meter with the detector in the plane of the treatment area.